A novel in-situ preparation of N-rich spherical porous carbon as greatly enhanced material for high-performance supercapacitors. (January 2021) - Gang, Xu; Krishnamoorthy, Mohanapriya; Jiang, Wenchao; Pan, Junqing; Pan, Zhigang; Liu, Xiaoguang
Abstract: Herein, a new approach to form the N-rich spherical porous carbon from direct carbonization of metal-organic framework based Zn-2, 4, 6-tris(3, 5-dicarboxylphenylamino)-1, 3, 5-triazine structure without using any external doping and templates is proposed. During the carbonization process, Zn atoms, carboxyl and other functional groups are removed at high temperature, resulting in formation of mixed micro and mesopores with an increased surface area of 1826 m 2 g −1 and nitrogen content of 11.37%. Benefiting from the high content of graphitic N and spherical structure, N-rich spherical porous carbon exhibits high specific capacitance of 386.3 F g −1 at 1 A g −1 along with superb cyclic stability of 97.8% capacitance retention after 100, 000 cycles at 150 A g −1 . Besides, the N-rich spherical porous carbon-based symmetric supercapacitor offered specific capacitance values of 186.9 and 98.6 F g −1 at 1 and 150 A g −1, respectively. This device delivers an appreciable energy density (50.9 Wh kg −1 ) at the corresponding power density (1.6 kW kg −1 ), indicating that it will be a new approach for the preparation of spherical porous carbon derived from MOFs for the power supercapacitors. Graphical abstract: Image 1 Highlights: Hierarchically N-rich spherical porous carbon was prepared by using Zn-TDPAT MOF. The porous carbon were formed without any doping, template and activation processes. It has high surface area (1826 m 2 g −1 ) with satisfied capacitance of 386.3 F g −1 . It offers a very low decay rate (2.9%) after 1.0 × 10 5 cycles at ultra-high current. The assembled EDLC shows high energy density of 50.9 Wh kg −1 at 1.6 kW kg −1 .